1999
DOI: 10.12968/bjon.1999.8.18.6484
|View full text |Cite
|
Sign up to set email alerts
|

Improving primary health care for people with learning disabilities

Abstract: 'Signposts for Success' (Department of Health (DoH), 1998a) states that specialist learning disability services (SpLDS) must promote liaisons with, and offer specialist advice to, primary healthcare teams (PHCTs). With the advent primary care groups (DoH, 1998b), genuine collaboration and partnership-forging is necessary and timely to prevent people with learning disabilities being excluded from healthcare services. The project described in the article had three broad aims: first, to establish a practice regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(49 citation statements)
references
References 9 publications
1
48
0
Order By: Relevance
“…This supports the finding of the previous review that studies consistently provide evidence of health checks leading to targeted actions to address identified health needs (Baxter et al, 2006;Bollard, 1999;Hunt et al, 2001Hunt et al, , 2006Lennox et al, 2006Lennox et al, , 2007Lennox et al, , 2008Lennox et al, , 2010Lennox et al, , 2011Martin, Axon, et al, 2004;Martin, Philip, et al, 2004;McConkey et al, 2002;Webb & Rogers, 1999). In the UK, an audit of actions resulting from health checks for 190 participants, of whom 93 had new health needs identified, indicated that management had been initiated for 90% of identified needs by the time of the audit and treatment concluded for 61% of needs (Baxter et al, 2006).…”
Section: Health Actions Resulting From Health Checkssupporting
confidence: 88%
See 2 more Smart Citations
“…This supports the finding of the previous review that studies consistently provide evidence of health checks leading to targeted actions to address identified health needs (Baxter et al, 2006;Bollard, 1999;Hunt et al, 2001Hunt et al, , 2006Lennox et al, 2006Lennox et al, , 2007Lennox et al, , 2008Lennox et al, , 2010Lennox et al, , 2011Martin, Axon, et al, 2004;Martin, Philip, et al, 2004;McConkey et al, 2002;Webb & Rogers, 1999). In the UK, an audit of actions resulting from health checks for 190 participants, of whom 93 had new health needs identified, indicated that management had been initiated for 90% of identified needs by the time of the audit and treatment concluded for 61% of needs (Baxter et al, 2006).…”
Section: Health Actions Resulting From Health Checkssupporting
confidence: 88%
“…A further newly identified study in Northern Ireland analysed information gathered from GP returns regarding health checks to the Health and Social Care Board, as well as a sample of patient satisfaction questionnaires from GP practices and feedback from primary care staff obtained at a consultation workshop (McConkey, 2013). A number of other studies, three of which were newly identified, used questionnaires, interviews, or workshop discussions to look at the views of service users, carers, GPs or practice nurses with regard to health checks (Barr et al, 1999;Bollard, 1999;Cassidy et al, 2002;Chapman, 2012;Lennox et al, 2013;Martin, Roy, Wells, & Lewis, 1997;McConkey et al, 2002;Walmsley, 2011) and one was based on a cross-sectional survey of community learning disability nursing services in Scotland (McKenzie & Powell, 2004). Of other newly identified articles: one study used focus groups to look at the views of service users regarding health checks and this was pooled with additional focus group data looking at service user experiences of primary healthcare (Perry et al, 2014); clinical audit was used to evaluate health checks in relation to the recording of information for specific questions (Codling, 2007(Codling, , 2012; and inclusive research involving people with intellectual disabilities visiting GP surgeries has been reported (Michell, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Uncontrolled studies in the UK have reported a variety of benefits of health checks, including improved seizure control and weight management. [33][34][35][36] These UK studies were small, with fewer than 100 participants. One larger before-and-after study of a domiciliary preventative intervention in the USA found a reduction in self-reported pain, falls and emergency room visits, 37 whereas another larger US study suggested that health screening may help to resolve psychiatric problems by identifying physical problems.…”
Section: Evidence Base For Annual Health Checksmentioning
confidence: 99%
“…A possible solution to this lack of expertise is to make active links with those who are experienced and skilled in working with people with intellectual disabilities and community nurses are the obvious choice [24]. Whether community intellectual disability nurses fulfil the role of health facilitators for individuals or have more consultative role within the GP practice as a whole, both strategies would seem like an improvement on the current situation.…”
Section: Joint Workingmentioning
confidence: 99%